Ultrasound-Guided Intervention for Treatment of Trigeminal Neuralgia: An Updated Review of Anatomy and Techniques - Abdallah El-Sayed Allam; Adham Aboul Fotouh Khalil; Basma Aly Eltawab; Wei-Ting Wu; Ke-Vin Chang (Pain Research and Management)
Orofacial myofascial pain is prevalent and most often results from entrapment of branches of the trigeminal nerves. It is challenging to inject branches of the trigeminal nerve, a large portion of which are shielded by the facial bones. Bony landmarks of the cranium serve as important guides for palpation-guided injections and can be delineated using ultrasound. Ultrasound also provides real-time images of the adjacent muscles and accompanying arteries and can be used to guide the needle to the target region. Most importantly, ultrasound guidance significantly reduces the risk of collateral injury to vital neurovascular structures. In this review, we aimed to summarize the regional anatomy and ultrasound-guided injection techniques for the trigeminal nerve and its branches, including the supraorbital, infraorbital, mental, auriculotemporal, maxillary, and mandibular nerves.